2015
DOI: 10.1002/adfm.201500969
|View full text |Cite
|
Sign up to set email alerts
|

ReS2‐Based Field‐Effect Transistors and Photodetectors

Abstract: Atomically thin 2D layered transition metal dichalcogenides (TMDs) have been extensively studied in recent years because of their appealing electrical and optical properties. Here, the fabrication of ReS2 field‐effect transistors is reported via the encapsulation of ReS2 nanosheets in a high‐κ Al2O3 dielectric environment. Low‐temperature transport measurements allow to observe a direct metal‐to‐insulator transition originating from strong electron–electron interactions. Remarkably, the photodetectors based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
247
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 316 publications
(271 citation statements)
references
References 43 publications
19
247
3
Order By: Relevance
“…This study is in good agreement with our experiment results. As shown in Figure 1 By comparing to ReX2, WTe2 has shown many similarities, including the same distorted 1T lattice structure, similar anisotropic electronic, optical, vibrational and thermal dynamical properties [8,9,11,[16][17][18][19][20][21][22][23][24][25]. Both materials exhibit metal atom chains along one of the principle axes as shown in Figure 2 and Figure 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study is in good agreement with our experiment results. As shown in Figure 1 By comparing to ReX2, WTe2 has shown many similarities, including the same distorted 1T lattice structure, similar anisotropic electronic, optical, vibrational and thermal dynamical properties [8,9,11,[16][17][18][19][20][21][22][23][24][25]. Both materials exhibit metal atom chains along one of the principle axes as shown in Figure 2 and Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the low lattice symmetry and unique band structures, ReX2 show pronounced in-plane anisotropic properties with possible device applications. For example, few-layer ReX2 sheets have been demonstrated as channel materials for field effect transistors [8,9,11], integrated digital inverters [9] and photodetectors [11,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For TMDCs, single channel photodetectors, CVD synthesis with solid-phase metal oxide and sulfur precursors are widely used because of the easy synthesis approach, large single crystal domain, and high mobility. Photodetectors based on CVD MoS 2 [113,131], MoSe 2 [132,133], ReS 2 [63,114], ReSe 2 [134], SnS 2 [135,136], SnSe 2 [137], and WS 2 [110,122] have been studied recently. Jing et al reported a MoS 2 phototransistor array that can detect room light illumination [138].…”
Section: Single Channel Photodetectorsmentioning
confidence: 99%
“…The photoconductive gain, typically induced by the trapping of charge carrier, can provide response to optical signals with frequencies ranging between 1 kHz to 3 kHz (Figure 5a,b) [100]. The time constant of TMDCs and the BP single channel photodetector is commonly between several milliseconds to hundreds of seconds (one example of WS 2 photodetector shown in Figure 5c,d) [10,[112][113][114][115][116][117]. Hence, these photodetectors can be potentially applied in a low light intensity and frequency device, while photo-electron gain is mainly contributed by the photovoltaic effect when the time constant is large.…”
Section: Single Channel Photodetectorsmentioning
confidence: 99%